Strategies for sustainable technologies and innovations - McIntyre, John R.; Ivanaj, Silvester; Ivanaj, Vera.; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2013)
There is no debate about the fact that a "business as usual" approach is an environmentally unsustainable one. Given the magnitude of the environmental challenges the world faces today, extensive changes in corporate strategies and significant innovation advances are absolutely necessary if we are to avoid substantial decreases in our quality of living. This set of internationally recognized authors provides some fresh and informative perspectives on this topic along with a path for a more sustainable future. Mark Ferguson, University of South Carolina, USCorporations across the world are becoming increasingly aware of the threat of environmental degradation and the growing importance of sustainable business practices. This raises a vital question: How can for-profit firms (and other profit-conscious enterprises such as government organizations) implement more environmentally friendly policies without sacrificing profitability? This innovative volume tackles that complex question, offering detailed recommendations for making strategic technological choices that are economically advantageous, ecologically sustainable and socially responsible.Expert contributions examine the contextual factors that affect implementation of more sustainable technology and innovation practices, offering a number of empirical methodologies to describe and explain these multidimensional influences. What emerges is a compelling argument in favor of balanced strategies that merge profitability concerns with ecological consciousness, allowing for controlled sustainable development and stable, long-term economic success. Discussion of companies in both developed and emerging countries makes this book useful on a truly global scale.Students and professors of business, management studies and economics will find much to admire in this path-breaking volume. Managers, policymakers and other practitioners will also benefit greatly from this books timely and insightful recommendations.
pt. I. Building sustainable technology and innovation systems -- pt. II. Strategic implications and assessment.
Includes bibliographical references and index.
Keywords: Business enterprises -- Environmental aspects; Technological innovations -- Management; Sustainable development; Electronic books